Polymorphic CAG repeats of the androgen receptor gene and rheumatoid arthritis. Issue 8 (1st August 1999) - Kawasaki, Taku; Ushiyama, Toshio; Ueyama, Hisao; Inoue, Koji; Mori, Kanji; Ohkubo, Iwao; Hukuda, Sinsuke
Abstract : OBJECTIVE: In view of the possible role of androgens in the pathogenesis of rheumatoid arthritis (RA), this study investigated the association between repeat lengths of CAG microsatellites of the androgen receptor (AR) gene and RA. METHODS: The number of CAG repeats in exon 1 of the AR gene was determined in 90 men and 276 women with RA, as well as in 305 male and 332 female controls. RESULTS: The male RA patients tended to have shorter repeats than the male controls (22.5 versus 23.1, p=0.07), whereas the female RA patients had similar repeats to the female controls (22.7 versus 22.9, p=0.17). Patients of both sexes were divided into younger and older age at onset groups, and compared with younger and older controls. Younger onset male RA patients had significantly shorter CAG repeat lengths than the younger male controls (21.8 versus 23.2, p=0.007) or the older onset male RA patients (21.8 versus 23.2, p=0.04). Older onset male RA and both younger and older onset female RA patients had similar CAG repeat lengths when compared with their controls. Neither seropositivity nor rheumatoid nodule positivity had a significant relation with CAG repeat lengths. CONCLUSION: Shorter CAG repeats of the AR gene, presenting high levels of transactivation activity, are related to younger age onset male RA, suggesting the possible role of androgens as a modulating factor.